Current status of public health awareness and roles within medical institutions in eastern China - Wu, Yuchen; Zhang, Chuanfeng; She, Quan; Zheng, Wei; Lu, Kai; Wang, Furu (Frontiers in Public Health, 2025)
ObjectiveTo examine the current landscape of public health functions and the level of cognition among medical staff across various medical institutions in Jiangsu Province, ultimately aiming to provide a theoretical framework for constructing a hospital public health work model under the integrated medical and defense system.MethodsA mixed-methods approach involving questionnaires and semi-structured interviews was employed to assess the establishment and operational status of public health departments within medical institutions, staffing scenarios, comprehension of public health tasks, and the degree of emphasis placed on them.ResultsOur findings reveal that 70.6% of medical institutions possess standalone public health departments, with a median of 5 full-time public health personnel, predominantly from the nursing profession. Significant disparities were observed in the demographics, educational backgrounds, majors, job classifications, and titles of public health personnel across different medical institution levels. Additionally, 68.4% of institutions have formed public health management committees, and 77.2% shoulder ≥10 public health responsibilities. Notably, 99.2% of medical staff endorse the importance of public health work within medical institutions, and 98.3% advocate for the support of disease control agencies. Interviews further unveiled a predominantly positive stance among medical institution leaders toward the integration of public health and medical prevention.ConclusionMedical institutions of Jiangsu Province necessitate enhanced public health staffing, improved organizational structure and responsibility divisions for public health work, and a boost in knowledge levels to effectively carry out public health responsibilities. Furthermore, policy support and multi-stakeholder engagement are crucial to mobilize hospitals to take proactive initiatives.